STRATEGI PENGEMBANGAN USAHA KERUPUK IKAN DI DESA PESANGGRAHAN, LAREN, LAMONGAN - Irawati, Desrina Yusi; Bellanov, Agrienta; Canariesa, Armadeo Ruben; Valentino, Teofilus (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
Pesanggrahan Village is one of the villages in the Lamongan district, located on the banks of the Bengawan Solo River. The fish caught by local fishermen inspires residents to innovate in producing crackers. One of the fish crackers in Pesanggrahan village is the cracker produced by Afisfa Kitchens. Afisfa Kitchen’s crackers have drawbacks, namely that the crackers quickly go "rancid," the packaging label is straightforward, and the business does not have good financial management. The service programs at Afisfa Kitchen’s crackers include developing spinner machines, changing label designs, and training in business financial management. Service activities include discussions, preparing spinner machines, counseling, and training. The result of the service program that has been carried out is that using a spinner machine can reduce oil so that the crackers can last longer. Label designs were made for three types of crackers: labels for tilapia, gabus, and milkfish. Labels look more attractive and informative. The results of financial management training produce monthly financial reports. All community service activities ran smoothly and were attended with enthusiasm.